Learning beyond the classroom : education for a changing world - Bentley, Tom, 1973- (Routledge, 1998)
Education has become one of our major concerns, at the heart of any strategy for prosperity and social cohesion. But young people are having more difficulty than ever before in adapting to the world they will enter as adults. Tom Bentley argues that if education is to meet the emerging challenges of the twenty-first century, we must recognise that learning takes place far beyond the formal education sector. We cannot rely solely on dedicated teachers to deliver the understanding and personal qualities young people will need. Instead we must connect what happens in schools to wider opportuni.